2019
DOI: 10.3389/fonc.2019.01269
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Three-Long Non-coding RNA Signature Predicts Prognosis in Colorectal Cancer Patients

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide, whose morbidity and mortality gradually increased. Here, we aimed to identify and access prognostic long non-coding RNAs (lncRNAs) associated with overall survival (OS) in CRC. Firstly, RNA expression profiles were obtained from The Cancer Genome Atlas (TCGA) database, and 439 CRC patients were enrolled as a training set. Univariate Cox analysis and the least absolute shrinkage and selection operator analysis (LASSO) were performed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…High expression of BANCR could be in positive correlation with CRC metastasis and poor prognosis, which was consistent with our findings (30). Consistently, it has been reported that LINC01602 could predict poor prognosis of CRC patients (31). However, the mechanisms of GK-IT1, CECR7, and LINC02188 in CRC metastasis remain unclear.…”
Section: Discussionsupporting
confidence: 91%
“…High expression of BANCR could be in positive correlation with CRC metastasis and poor prognosis, which was consistent with our findings (30). Consistently, it has been reported that LINC01602 could predict poor prognosis of CRC patients (31). However, the mechanisms of GK-IT1, CECR7, and LINC02188 in CRC metastasis remain unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, identifying effective lncRNAs to predict the prognosis of cancer patients has gradually attracted various levels of scientific research. Moreover, researchers have explored many lncRNA predictive models to determine the prognosis of tumor patients including liver cancer, pancreatic cancer, lung cancer, esophageal cancer, colorectal cancer, breast cancer, among others ( Gu et al, 2018 , 2019 ; Zhao et al, 2018 ; Liu et al, 2019 ; Ma and Deng, 2019 ; Zhou et al, 2019 ; Shen et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ). A study by Ma found that four lncRNA signature can effectively distinguish high-risk and low-risk patients in liver cirrhosis and liver cancer patients thereby accurately predict the prognosis of liver cancer patients ( Ma and Deng, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the raw count data were normalized by transcripts-per-million method and underwent a log2 transformation. LncRNAs were reannotated by gene symbol based on the gene annotation file “gencode.v35.long_noncoding_RNAs,” which was downloaded from the GENCODE website ( https://www.gencodegenes.org/human/ ) (Liu et al, 2019b ). ARGs were obtained from the HADb (Human Autophagy Database, http://www.autophagy.lu/ ).…”
Section: Methodsmentioning
confidence: 99%